A Comparative Study of the African and Western Mediation Models: The Case of Ghana - Swaniker, A.J. (University of Ghana, 2019)
Mediation, a mechanism for the resolution of dispute, has been an ancient practice for several civilizations. Mediation was a form of resolving disputes in Africa, Ghana in particular before the coming of the Europeans. In recent times, the origin of ADR mechanism has been a debate among the conflict resolution fraternity and academicians. Owing to the fact that mediation has been used in diverse civilizations, the conduct and process varies and usually tends to suit the cultural context of the people. Mediation, as part of the ADR spectrum, has been structured in a wholly Western perspective with no room for cultural variations. Given the above-mentioned trends the study aims at finding the relations between African and Western mediation models, what is common between the two models, disparities between them and how the similarities and disparities qualitatively affect the outcome of the effectiveness of mediation in Africa and the Western world. The research utilized the qualitative research method with data from both primary and secondary sources. The study revealed that both Africans and Westerners do have their own approach to mediation, it also revealed that the differences and commonalities qualitatively affect the outcome of the effectiveness of mediation in Africa and the Western world. The study shows that both models of mediation has the same aim thus to resolve conflict amicably. The study recommends that a blend of both mediation models has a high tendency of resolving disputes peacefully especially when parties have different cultural orientations
MA. International Affairs
Keywords: African; Western; Mediation; Ghana